Microfluidic study of competence regulation in Streptococcus mutans: environmental inputs modulate bimodal and unimodal expression of comX - Son, Minjun (2012)
Streptococcus mutans regulates genetic competence through a complex network that receives inputs from a number of environmental stimuli, including two signaling peptides designated as CSP and XIP. The response of the downstream competence genes to these inputs shows evidence of stochasticity and bistability and has been difficult to interpret. We have used microfluidic, single-cell methods to study how combinations of extracellular signals shape the response of comX, an alternative sigma factor governing expression of the late competence genes. We find that the composition of the medium determines which extracellular signal (XIP or CSP) can elicit a response from comX and whether that response is unimodal or bimodal across a population of cells. In a chemically defined medium, exogenous CSP does not induce comX, whereas exogenous XIP elicits a comX response from all cells. In complex medium, exogenous XIP does not induce comX, whereas CSP elicits a bimodal comX response from the population. Interestingly, bimodal behavior required an intact copy of comS, which encodes the precursor of XIP. The comS-dependent capability for both unimodal and bimodal response suggests that a constituent – most likely peptides – of complex medium interacts with a positive feedback loop in the competence regulatory network.